Pengaruh Produk Domestik Regional Bruto Dan Investasi Terhadap Pendapatan Asli Daerah Kabupaten/Kota Di Sumatera Barat - Andini, Sri Muthia; Shabri, Husni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This research aims to analyze the influence of Gross Regional Domestic Product (GRDP) and Investment on Original Regional Income (PAD) in Regencies/Cities in West Sumatra. The type of research used is empirical research with a quantitative approach method, the data source used is secondary data sources published by the Central Statistics Agency (BPS) and the Ministry of Finance. The data collection technique uses documentation obtained through related agencies or institutions, the data analysis technique uses panel data regression analysis techniques, then processed using the E-views 12 application. The results of the research show that GRDP does not have a significant effect on PAD in districts/cities in West Sumatra, investment has a significant influence on PAD in districts/cities in West Sumatra, as well as GRDP and investment has a significant influence on PAD District/City in West Sumatra. The implications of this research are that regional governments are expected to maintain and improve the investment climate and increase regional revenues in districts/cities in West Sumatra so that they remain in a more conducive situation, considering that GRDP and investment can contribute large increase in PAD in Regencies /Cities in West Sumatra.